Performance contracts in the procurement of primary care services under the national health insurance program and lessons learned from the Netherlands: A literature review - Evita Mutiara; Siti Rahima Kiram; Salsabila Firdausi; Cahya Arbitera; Riswandy Wasir (Indonesian Journal of Health Science, 2026)
Primary health care plays a crucial role in the National Health Insurance (JKN) program, making performance contracts essential for improving the quality and efficiency of services. Lessons learned from the Netherlands can serve as a reference for strengthening their implementation in Indonesia. This study evaluates performance contracts in the strategic procurement of primary health care services under the JKN program and identifies lessons from the Netherlands to improve service quality. This study is a literature review of eight articles published between 2017 and 2026 to analyze performance contracts in the procurement of primary care services under the JKN and lessons from the Netherlands. Performance contracts have proven effective in improving the efficiency and quality of primary care services when designed with balanced incentives between cost control and service quality achievement. The success of their implementation is highly dependent on relevant performance indicators, an integrated information system, and continuous monitoring and evaluation. The Dutch experience demonstrates that a combination of population-based payments, shared savings, contractual flexibility, and strong regulation can provide important lessons for strengthening strategic purchasing and improving the quality of primary care services within the JKN. Performance contracts have the potential to improve the efficiency and quality of primary care services if supported by relevant indicators, an integrated information system, and ongoing monitoring. Lessons from the Netherlands show that population-based payments, shared savings, and strong regulations can serve as a model for strengthening the implementation of performance contracts within the National Health Insurance (JKN) program.